(untitled) (Bangladesh Journal of Botany, 2025)
In the present study, 42 rice genotypes were evaluated for genetic variability, heritability, and trait associations for 13 traits to enhance resilience in direct-seeded conditions. Significant variation (ANOVA) was observed, with the widest range in seedling vigour index-I (1533.1-3708.8) and the narrowest in root-to-shoot ratio (1.13-2.55). High genotypic (GCV) and phenotypic (PCV) coefficients of variation, along with high heritability and genetic advance, were recorded for seedling vigour index-II (GCV: 25.06; PCV: 25.87), grain yield/plant (24.59; 25.39), germination index, seedling dry weight, shoot length, and root-to-shoot ratio, indicating strong genetic control and potential for phenotypic selection. Seedling vigour index-II (SVI-II) showed strong positive correlations with shoot dry weight (0.97**), shoot fresh weight (0.87**), and shoot height (0.95**), suggesting indirect selection of these traits could improve early vigour and yield in direct-seeded rice. The findings highlight traits with high heritability and genetic potential for breeding resilient genotypes. Bangladesh J. Bot. 54(4): 1027-1033, 2025 (December)